Base Sequence Context Effects on Nucleotide Excision Repair. (29th June 2010) - Cai, Yuqin; Patel, Dinshaw J.; Broyde, Suse; Geacintov, Nicholas E.
Abstract : Nucleotide excision repair (NER) plays a critical role in maintaining the integrity of the genome when damaged by bulky DNA lesions, since inefficient repair can cause mutations and human diseases notably cancer. The structural properties of DNA lesions that determine their relative susceptibilities to NER are therefore of great interest. As a model system, we have investigated the major mutagenic lesion derived from the environmental carcinogen benzo[ a ]pyrene (B[ a ]P), 10 S (+)- trans-anti -B[ a ]P-N 2 -dG in six different sequence contexts that differ in how the lesion is positioned in relation to nearby guanine amino groups. We have obtained molecular structural data by NMR and MD simulations, bending properties from gel electrophoresis studies, and NER data obtained from human HeLa cell extracts for our six investigated sequence contexts. This model system suggests that disturbed Watson-Crick base pairing is a better recognition signal than a flexible bend, and that these can act in concert to provide an enhanced signal. Steric hinderance between the minor groove-aligned lesion and nearby guanine amino groups determines the exact nature of the disturbances. Both nearest neighbor and more distant neighbor sequence contexts have an impact. Regardless of the exact distortions, we hypothesize that they provide a local thermodynamic destabilization signal for repair.